1998
DOI: 10.1007/s004649900659
|View full text |Cite
|
Sign up to set email alerts
|

Spilled gallstones after laparoscopic cholecystectomy

Abstract: Spillage of gallstones after laparoscopic cholecystectomy is fairly common and occurs in about 6% of patients. However, abscess formation with subsequent surgical therapy remains a minor problem. Removal of spilled gallstones is therefore not recommended for all patients, but an attempt at removal should be performed whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…B. Imagen coronal de RM potenciada en T2, en la cual se observa un trayecto fistuloso a la piel (flecha) en paciente con antecedente de CLP con cálculo abandonado en cavidad abdominal. flora normal del tracto gastrointestinal (1,18,20,21,22). Contrario a los cálculos, los clips quirúrgicos caídos parecen ser un hallazgo mucho menos significativo clínicamente, ya que no están asociados con un mayor riesgo de formación de absceso y, por lo tanto, no necesitan seguimiento o remoción quirúrgica.…”
Section: Discussionunclassified
“…B. Imagen coronal de RM potenciada en T2, en la cual se observa un trayecto fistuloso a la piel (flecha) en paciente con antecedente de CLP con cálculo abandonado en cavidad abdominal. flora normal del tracto gastrointestinal (1,18,20,21,22). Contrario a los cálculos, los clips quirúrgicos caídos parecen ser un hallazgo mucho menos significativo clínicamente, ya que no están asociados con un mayor riesgo de formación de absceso y, por lo tanto, no necesitan seguimiento o remoción quirúrgica.…”
Section: Discussionunclassified
“…A variety of instruments, such as laparoscopic spoons, Dormia Baskets, graspers, and suction devices as well as the use of peritoneal lavage, are all recommended interventions for stone retrieval. 16 Moreover to minimize any further stone spillage, an attempt should be made to close any defects in the gallbladder wall. 17 Conversion to open surgery remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, routine conversion to laparotomy is not indicated, although it should be considered in patients with suspected bile contamination and spillage of multiple stones. 14,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…This is obviously a matter of concern because additional studies reported incidents of gallbladder perforation during laparoscopic surgery varying from 10% to 40%, a 7.3% incidence of gallstone spillage, and an estimated 33% of unretrieved gallstones. 813,14 …”
Section: Introductionmentioning
confidence: 99%